Secondary metabolites from marine bacterium Streptomyces sp. G039 - Quyen, Vu Thi; Nam, Vu Van; Hieu, Tran Van; Vinh, Le Cong; Mai Huong, Doan Thi; Hong Minh, Le Thi; Murphy, Brian; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Nine secondary metabolites, cylo-(Leu-Pro) (1), cyclo-(Pro-Tyr) (2), indole-3-carboxylic acid (3), 3-hydroxyacetylindole (4), phenethyl 2-phenyl acetate (5), n-butyl–isobutyl phthalate (6), 4-(2-hydroxyethyl) phenol (7), 2-phenylacetic acid (8), and uracil (9) were isolated and identified from marine Streptomyces sp. G039. Their structures were determined by spectroscopic analysis including MS and 2D NMR, as well as by comparison with reported data in the literature.